1997
DOI: 10.1177/036354659702500206
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Repair of Achilles Tendon Ruptures

Abstract: We performed a series of repairs of Achilles tendon ruptures in athletes using suture augmented with a polyethylene terephthalate mesh synthetic graft. No postoperative immobilization was used. The 29 patients were aged 25 to 54 years and all practiced sports a minimum of 4 hours weekly. At the followup, ranging from 6 months to 5 years, ankle mobility was normal in all but one patient, who had lost 15 degrees of extension. All the patients were able to do a series of 10 single-limb heel raises without any imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Six studies did not report patient sex[38,61,75,85,102,126] and five studies did not report patient age[45,62,73,75,80]. Eighty-five of the studies reported RTP measure (RTP methodology sub-group 1) and 23 were classified as lacking RTP measure (methodology sub-group 2).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies did not report patient sex[38,61,75,85,102,126] and five studies did not report patient age[45,62,73,75,80]. Eighty-five of the studies reported RTP measure (RTP methodology sub-group 1) and 23 were classified as lacking RTP measure (methodology sub-group 2).…”
Section: Resultsmentioning
confidence: 99%
“…Surgical techniques include simple end-to-end suture [1,2,16,17,19] and several procedures for augmented reconstruction. [5,13,22] Augmented reconstruction, initially developed for chronic or neglected ruptures, is now also used for acute ruptures by some authors [22]. Simple end-to-end suture is easier and can be performed through a more limited approach [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Options include V-Y sliding tendinous flaps as in this case, 1 tendon transfer or augmentation with Plantaris, Flexor hallucis longus, 10,11 Peroneus longus 5 or Flexor Digitorum longus tendons, 7 or synthetic replacements. 3,4 In conclusion, this case reports an unusual cause to an uncommon injury in this country and highlights the importance of clinical suspicions from diagnostic signs against an otherwise unremarkable history.…”
Section: Discussionmentioning
confidence: 63%